A Proposed Model to Improve the Skills of Mathematical Thinking (C.A.S.M.E) and Its Impact on The Achievement of Students in the Fifth Grade in Solving the Mathematical Problems - HamzahAbed AL-Ubodi, Ahmed; ., . (International Journal of Engineering and Technology, 2018)
The current research aims to design a proposed teaching model to improve the thinking skills of the students in the fifth grade of the primary and to know its effect on their achievement solving mathematical problems. The proposed model was used CASME, which means accelerating mental growth through scientific and mathematical education. Acronym to Cognitive Acceleration Through Science and Mathematics Education.This model combines two models: the CASE model and the CAME model, as well as the modification of some steps and procedures that help in the process of improving thinking and be compatible at the same time to the process of accelerating thinking.The sample was selected randomly  (62) students from the university mixed primary school, and the sample was divided into two, the first experimental group (31) students and the second group control (31) students, and the search tools were three, the first questionnaire for thinking, Second Pre- test and third Post-test, dimension It was sure to have psychometric properties, has been used Cooder Richardson equation 20,(t)test  for two independent samples and(t)  test for statistical samples interconnecting means, and the results showed .There were statistically significant differences between the pre and post test of the experimental group, as well as the existence of statistically significant differences between the post-test of the two research groups, both in favor of the proposed teaching model. In the end of the results, a set of recommendations were written.